PEMAHAMAN SURAT-SURAT PENDEK AL-QUR’AN TENTANG TOLERANSI DAN IMPLIKASINYA BAGI PENGEMBANGAN SIKAP PLURALISME - Syah, Darwyan (Universitas Islam Negeri Raden Intan Lampung, 2013)
This study aims to describe the level of understanding short letters of the Qur’an about tolerance and pluralism attitude; and analyze the effects of short letters of understanding Qur’an about tolerance towards pluralism attitude. This research on religius junior secondary school students Nurul Yaqin Ciledug Tangerang City Banten Province. The instrument for understanding short letters of the Qur’an about tolerance using multiple choice test with three option. Pluralism attitude instrument using a questionnaire with three options. The results show: Firstly, the level of understanding short letters of the Qu’an about tolerance reaches 74.31 % in the high category and the level of pluralism attitude reaches 82.48 % included in the high category. Secondly there is positive and significant understanding of short letters of the Qur’an about tolerance towards pluralism attitude. The influence understanding of short letters of the Qur’an about tolerance to pluralism attitude of 29.52 % . The rest is influenced by other factors remains to be investigated. The higher understanding of short letters of the Qur’an about tolerance the higher attitude of pluralism. Increased pluralism student attitudes can be improved through an increased understanding of the short letters of the Qur’an about tolerance.